Doctor Who - The Tomb of the Cybermen - Barry, Morris; Hamilton, Peter; Troughton, Patrick; Hines, Frazer; Watling, Deborah (BBC Worldwide, 2002)
The surprise discovery of the long-lost "Tomb of the Cybermen" in Hong Kong is considered to be one of the greatest Doctor Who finds of the past 15 years; until then, only pieces of Patrick Troughton's first two seasons, including precious little of the work of Deborah Watling (Victoria), existed at all. [www.gallifreyone.com]
Keywords: DVD-Video